Differential and variational formalism for an acoustically levitating drop - Chernova, M.O.; Lukovsky, I.O.; Tymokha, O.M. (Нелінійні коливання, 2015)
Starting with the most general problem on interface waves between two ideal fluids, treated here as an ullage gas and a liquid, respectively, and separating fast and slow time scales, differential and variational formalism for an acoustically levitating drop and its time-averaged shape (the drop vibroequilibrium) are developed. The drop vibroequilibria can differ from spherical shape; stable vibroequilibria are associated with local minima of the quasipotential energy whose analytical form is also derived in the present paper